PANDANGAN TOKOH AGAMA TERHADAP PENGELOLAAN ZAKAT FITRAH UNTUK MELUNASI HUTANG PEMBANGUNAN MASJID: Studi Kasus di Dusun Kalipakem Desa Donomulyo Kecamatan Donomulyo Kabupaten Malang - Bahrul Ulum (Jurnal Penelitian Ilmiah INTAJ, 2023)
The management of zakat fitrah in Kalipakem Donomulyo Malang is often carried out by takmir of mosques and prayer rooms. Zakat fitrah is not only distributed to the poor, but is also distributed to finance the construction of mosques/mushalas. This study aims to describe the management of zakat in Kalipakem and to analyze the views of the religious leaders of the hamlet on the management of zakat fitrah for mosque construction debts. It is a qualitative research. The collecting data method is interviews and documentation. The data analysis applied includes the stages of data reduction, data presentation, and drawing conclusions. The overall results of the data that have been analyzed illustrate that: 1) for the construction of a mosque in Kalipakem Donomulyo is interpreted as fi ifÄ« sabÄ«l AllÄh Â and ghÄrim. The meaning of FÄ« sabÄ«l AllÄh Â is defined as the allocation of consumption needs and building material funds during the mushala construction process. Zakat distributors for the construction of mosques are not official `Amil. 2) The views of religious leaders regarding the distribution of zakat fitrah for the construction of mosques are divided into two categories, namely agreeing with the terms and not agreeing. The Ulama group that agreed was from LDII, NU, and MUI. While Muhammadiyah has a different view, disagreeing with the distribution of zakat fitrah for the construction of mosques.